The Investigation of the Effects of Enalapril and Losartan on Ghrelin Immunoreactivity in Kidney of Streptozotocin-Induced Diabetic Rats - Donder, Emir; Dogan, Murat Mehmet; Kuloglu, Tuncay; Dabak, Özlem Dürrin; Kocaman, Nevin; Ozkan, Yusuf (Fırat University, 2013)
Objective: The aim of this study was to examine the effects of enalapril and losartan on ghrelin immunoreactivity in the kidney tissues of rats with streptozotocin (STZ) induced diabetes. Materials and Methods: The study involved 28 Wistar albino rats. The rats were allocated to four groups: control group (n=7), diabetes (DM) group (n=7), DM + enalapril group (n=7) and DM + losartan group (n=7). DM, DM + enalapril and DM + losartan groups were administered a single dose of 50 mg/kg of STZ, intraperitoneally. The rats in the treatment groups were orally administered 5 mg/kg/day of enalapril and 10 mg/kg/day of losartan, starting with the onset of diabetes. At the end of the fourth week of the experiment, rats were decapitated. Kidney tissues collected from the animals were processed by using routine histological techniques. Ghrelin immunoreactivity was determined by avidin-biotin-peroxidase method. Results: Ghrelin immunoreactivity in the distal tubules was moderate (++) in the control group and severe (+++) in the diabetic group. In the distal tubules of the treatment groups, ghrelin immunoreactivity was observed to be moderate (++), similar to the control group. Conclusion: It was determined that enalapril and losartan were effective against ghrelin immunoreactivity in the diabetic rat kidney tissues.

Amaç: Bu çalışmada, streptozotosin (STZ) ile deneysel olarak oluşturulan diyabetik sıçanların böbrek dokusunda, enalapril ve losartan'ın ghrelin immunreaktivitesi üzerine etkilerinin incelenmesi amaçlanmıştır. Gereç ve Yöntem: Çalışmada 28 adet erişkin, dişi Wistar albino cinsi sıçan kullanıldı. Deney hayvanları Kontrol grubu (n=7), diyabetik (DM) grup (n=7), DM + Enalapril (n=7) ve DM +Losartan (n=7) olmak üzere dört gruba ayrıldı. Diyabetik, DM + Enalapril ve DM +Losartan gruplarına 50 mg/kg olacak şekilde tek doz STZ (Sigma Chemical Co Louis Missouri) 0,1 M Fosfat-sitrat tamponunda ( pH: 4,5) çözdürülerek intraperitoneal olarak uygulandı. Tedavi gruplarındaki sıçanlara diyabetin başlangıcından itibaren 5 mg/kg/gün Enalapril ve 10 mg/kg/gün losartan oral olarak verildi. Deneyin 4. haftasının sonunda tüm gruptaki ratlar dekapite edildiler. Deney hayvanlarından alınan böbrek dokularına rutin histolojik teknikler uygulandı. Avidin-biotin-peroksidaz yöntemi ile ghrelin immünreaktivitesi belirlendi. Bulgular: Böbrek dokusunda distal tübüllerde kontrol grubunda orta şiddette (++), diyabetik grupta ise şiddetli (+++) ghrelin immünreaktivitesi gözlendi. Tedavi gruplarında ise distal tübüllerde her iki grupta da kontrol grubuna benzer şekilde orta şiddette (++) ghrelin immünreaktivitesi izlendi. Sonuç: Diyabetik sıçanların böbrek dokusunda enalapril ve losartanın ghrelin immunreaktivitesi üzerine etkili olduğu belirlendi.
Deneysel Diyabetik Sıçan Böbrek Dokusunda Enalapril ve Losartan'ın Ghrelin İmmunreaktivitesi Üzerine Etkilerinin İncelenmesi